Anaerobic capacity changes of the national freestyle wrestlers during the Olympic qualification competition period - Sever, O.; Gönülates, S.; Bayrakdar, A.; Demirhan, B.; Geri, S.; Zorba, E. (Journal of Education and Training Studies, 2017)
This study aimed to evaluate the national level wrestlers` anaerobic capacity through the preparation and qualification periods for Rio 2016 summer Olympic Games. For this manner, 10 national level freestyle wrestlers`(age 22,10 ± 3,21; weight 64,75 ±6,34; height 164,31 ± 4,75) anaerobic outputs measured 3 times in three month intervals with Bosco repeated jump test. Peak Jump(cm), Flight time, average power, average power/weight, first 15sec average jump height, last 15sec average jump height, fatigue index scores analyzed with repeated measures Anova. Mean power/weight output of the wrestlers increased from 20,42 W/kg to 21,28 W/kg(4,21 %) and fatigue index is decreased from 1,185 to 1,142 (3,62 %). However, this increase was not statistically significant (p<0,05). In six months of qualification and preparation period wrestlers` anaerobic capacity did not changed and it is thought to have been caused by some reasons such as having already reached a certain anaerobic peak level or athletes` competition level and frequency which might made it difficult for them to have a proper periodization during the year.